Isolation, cloning and molecular analysis of ag85a and tb10.4 genes from Mycobacterium tuberculosis - Rashidian, Samira; Derakhshan, Mohammad; Aryan, Ehsan; Teimourpour, Roghayeh; Gholoobi, Aida; Meshkat, Zahra (Archives of Medical Laboratory Sciences, 2019)
Background: Novel tuberculosis (TB) vaccines that aim to boost and/or replace Bacillus Calmette-Guerin (BCG) are currently in development. DNA vaccines can stimulate both humoral and cell-mediated immunity in different animal models of TB and is thought to be a promising strategy in the development of new vaccines against TB. The aim of this study was to design and construct a DNA vaccine encoding ag85a and tb10.4 fusion genes of Mycobacterium tuberculosis. Materials and Methods: tb10.4 fragment was amplified by PCR and the product was digested with restriction enzymes. Next, it was cloned into the pcDNA3.1+ plasmid. The ag85a gene and pcDNA3.1+/tb10.4 plasmid were digested by EcoRI and BamHI restriction enzymes. Constructed vector was sequenced. The molecular analysis was done using bioinformatics software. New chimeric vector containing ag85a-tb10.4 genes were purified. Expression of pcDNA3.1+/tb10.4-ag85a plasmid was confirmed in eukaryotic cells. Results: Fragments of 297 bp for tb10.4 and 1017 bp for ag85a were observed in agarose gel electrophoresis. Alignment of ag85a-tb10.4 genome sequence with reference genes in GenBank showed exact identities that indicate correction of all cloning procedures. Transfection of eukaryotic cells with pcDNA3.1+/tb10.4-ag85a vector and existence of tb10.4-ag85a fusion gene were both confirmed with RT-PCR. Conclusion: In this study, tb10.4 and ag85a genes were isolated from Mycobacterium tuberculosis H37Rv strain and cloned into pcDNA3.1+. Also, the capability of constructed vector in producing fusion ag85a-tb10.4 protein was confirmed with RT-PCR. pcDNA3.1+/tb10.4-ag85a vector can be used for further studies in future.